Treated Plasmodium berghei infected pregnant mice by Andrographis paniculata tablet (AS201-01) decreasing the TLR-4 expression and apoptosis index of placental tissue - Budi Prasetyo, Diantri Nari Ratih, Yustinasari, Hilkatul Ilmi, Lidya Tumewu, Aty Widyawaruyanti & (Journal of Applied Pharmaceutical Science, 2018)
Objective: This study aimed to evaluate the effect of Andrographis paniculata tablet (AS201-01) in decreasing expression of Toll-Like Receptor-4 (TLR-4) and apoptosis index of placental tissue of Plasmodium berghei infected pregnant mice. Material and Methods: A total of 24 pregnant mice were divided into 4 groups, G1 was uninfected pregnant mice group, G2 was untreated Plasmodium berghei infected pregnant mice, G3 was P. berghei infected pregnant mice treated with AS201-01 tablet and G4 was P. berghei infected pregnant mice treated with dihydropiperaquine-phosphate (DHP) tablets. All mice were sacrifice at day 15th of pregnancy and the placenta was collected. The TLR-4 expression and apoptosis index were evaluated using immunohistochemistry assay. Results: The TLR-4 expression and apoptosis index on G3 was lower than G2 and showed a statistically significant difference (P = 0.00). The TLR-4 expression and apoptosis index of placental tissue in P. berghei infected pregnant mice which treated with AS201-01 tablet were decreased compared to untreated group and DHP tablet treated group as well. Conclusion: AS201-01 tablet containing ethyl acetate fraction of A. paniculata could decrease TLR-4 expression and apoptosis index of placental tissue in P. berghei infected pregnant mice.
Keywords: TLR-4 expression, Apoptosis index, Plasmodium berghei, in vivo assay, Andrographis paniculata tablet (AS201-01).